Relationship Between Care Burden and Religious Beliefs Among Family Caregivers of Mentally Ill Patients - Asadi, Parisa (Journal of religion and health, 2019)
Families are considered as primary sources of care for individuals suffering from mental disorders. However, one of the major stresses in families is the infliction of a family member with mental illnesses causing dysfunction in health dimensions or generally their quality of life. Currently, most experts believe that religion can affect physical health and other aspects of human life. So, the aim of this study was to investigate "the relationship between care burden and religious beliefs among family caregivers of mentally ill patients." This cross-sectional study was carried out in Iran on 152 families with mentally ill patients who were hospitalized in psychiatric wards. The sampling method was nonprobability and consecutive sampling method. The data collection instruments included a demographic characteristic questionnaire, Religious Beliefs, and Zarit Care Burden Questionnaires. The mean score for care burden was 30.99 (SD = 16.45). 5.9% of the participants reported a low level, and 39.5% experienced a moderate level of care burden. Moreover, the mean score for religious beliefs was 115.5 (SD = 13.49), and majority of the participants (70.4%) were endowed with strong religious beliefs. There were no significant associations between care burden and intensity of religious beliefs among the study samples (P = 0.483). Considering the results of this study indicating experience of moderate-to-high levels of care burden in families with mentally ill patients, it is recommended to consider such families and their religious beliefs as contributing factors in coping with challenges of mental disorders.